Impact of Injury Severity on Dynamic Inflammation Networks Following Blunt Trauma. Issue 2 (August 2015) - Almahmoud, Khalid; Namas, Rami A.; Abdul-Malak, Othman; Zaaqoq, Akram M.; Zamora, Ruben; Zuckerbraun, Brian S.; Sperry, Jason; Peitzman, Andrew B.; Billiar, Timothy R.; Vodovotz, Yoram
Abstract : ABSTRACT: Introduction: Clinical outcomes following trauma depend on the extent of injury and the host's response to injury, along with medical care. We hypothesized that dynamic networks of systemic inflammation manifest differently as a function of injury severity in human blunt trauma.Study Design: From a cohort of 472 blunt trauma survivors studied following institutional review board approval, three Injury Severity Score (ISS) subcohorts were derived after matching for age and sex: mild ISS (49 patients [33 males and 16 females, aged 42 ± 1.9 years; ISS 9.5 ± 0.4]); moderate ISS (49 patients [33 males and 16 females, aged 42 ± 1.9; ISS 19.9 ± 0.4]), and severe ISS (49 patients [33 males and 16 females, aged 42 ± 2.5 years; ISS 33 ± 1.1]). Multiple inflammatory mediators were assessed in serial blood samples. Dynamic Bayesian Network inference was utilized to infer causal relationships based on probabilistic measures.Results: Intensive care unit length of stay, total length of stay, days on mechanical ventilation, Marshall Multiple Organ Dysfunction score, prevalence of prehospital hypotension and nosocomial infection, and admission lactate and base deficit were elevated as a function of ISS. Multiple circulating inflammatory mediators were significantly elevated in severe ISS versus moderate or mild ISS over both the first 24 h and out to 7 days after injury. Dynamic Bayesian Network suggested that interleukin 6 production in severe ISS was affected by monocyte chemotactic protein 1/CCL2, monokine inducible by interferon γ (MIG)/CXCL9, and IP-10/CXCL10; by monocyte chemotactic protein 1/CCL2 and MIG/CXCL9 in moderate ISS; and by MIG/CXCL9 alone in mild ISS over 7 days after injury.Conclusions: Injury Severity Score correlates linearly with morbidity, prevalence of infection, and early systemic inflammatory connectivity of chemokines to interleukin 6. Abstract : Supplemental digital content is available in the text.